The Principles Of Spiritual Education In The Philosophical Heritage Of The Central Asian Peoples - Donabaevich, Haydarov Komil (International Journal of Psychosocial Rehabilitation, 2020)
This article considers the fact that in social-philosophical thought of the peoples of Central Asia aspiration to achieve spiritual perfection, maturity and enlightenment of man became a priority idea, analyzed philosophical views on the role of spiritually mature person in society. Imam al-Bukhari, Hakim Termezi, Imam Moturidi, Abduhalik Gijduvani, Amir Kulol, Bahauddin Naqshband, Abu Nasr Farobi, Abu Rayhan Beruni, Abu Ali Ibn Sino, who lived and worked in Central Asia, left a deep trace in the spiritual and enlightenment development of the world. Such great people as Farobi, Abu Rayhan Beruni, Abu Ali Ibn Sina were stars of spirituality of that time, and it turned out that they played a very important role in the cultural development of the region in the Middle Ages. This process shows that the integral development of religious and secular sciences is a characteristic feature of this period.